ULTRASONIC WAVE VELOCITIES AS A DIAGNOSTIC TOOL FOR THE QUALITY ASSESSMENT OF MARBLE - Weiss T.; Siegesmund S.; Rasolofosaon P.N.J. (My University, 2002)
Marbles are frequently used as building stones even if they mostly show a limited durability. Thus, different marbles with different fabric types and states of preservation have been investigated in order to constrain the interaction between fabric, state of deterioration and ultrasonic wave velocities. Experimental data reveal that the state of preservation of a marble is clearly documented by ultrasonic wave velocities of compressional waves. For a maximum porosity of up to 1% velocities determined on dry samples range from about 1 km s -1 to over 6 km s -1. Anisotropy of ultrasonic wave velocities is a common feature of marbles due to a lattice preferred orientation of the anisotropic rock-forming minerals calcite and dolomite. Pre-existing and thermally induced microcracks tend to increase this anisotropy. For Lasa marble, this increase can be explained by a coincidence of intrinsic anisotropy and the effect of pre-existing and thermally induced microcracks. For many marbles, velocities are reduced to at about 1 km s -1 as a consequence of thermal degradation due to only one heating cycle up to 100°C. Model calculations reveal that the velocity reduction is caused by cracks with an extremely small aspect ratio of about 0.005 or even less. The porosity associated with this very early stage of deterioration will not be increased significantly and thus, thermal degradation cannot be determined by other petrophysical measurements.